2023
DOI: 10.1128/spectrum.04365-22
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Host and Microbes in the Semen of Patients with Idiopathic Nonobstructive Azoospermia

Abstract: Idiopathic nonobstructive azoospermia is one of the great challenges in assisted reproductive therapy. Although microdissection testicular sperm extraction technology is currently available, many men with iNOA still face the problem of poor sperm retrieval and poor sperm quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…They set up three negative controls to exclude potential contaminants from air, tabletop and reagents. Contaminants in 16s RNA sequences were removed using the Decontam R package [9]. In agreement with Campbell et al, alpha diversity was similar between the groups; however, they found significant differences between groups at genera level; Ruegeria and Donghicola dominated the NOA group.…”
Section: Molina Et Al Assessed the V3-4 Hypervariable Region Of 16s R...supporting
confidence: 79%
See 4 more Smart Citations
“…They set up three negative controls to exclude potential contaminants from air, tabletop and reagents. Contaminants in 16s RNA sequences were removed using the Decontam R package [9]. In agreement with Campbell et al, alpha diversity was similar between the groups; however, they found significant differences between groups at genera level; Ruegeria and Donghicola dominated the NOA group.…”
Section: Molina Et Al Assessed the V3-4 Hypervariable Region Of 16s R...supporting
confidence: 79%
“…The culture or PCR-based methods used to inform this opinion are fundamentally flawed due to their inability to culture all bacteria [52]. More recently, advanced next-generation sequencing techniques (NGS) have allowed analysis of the seminal microbiome and identification of its unique composition [8][9][10][11] (Table 1). The exact origins of the bacteria within human seminal fluid remain unclear, and it is not known whether they represent transient colonisation or a static resident flora.…”
Section: The Human Seminal Microbiomementioning
confidence: 99%
See 3 more Smart Citations